(untitled) (Pedagogy of Higher and Secondary Education, 2010)
In article the theoretical analysis of a problem of improvement of quality of knowledge ofpupils at geography lessons is given; ways of improvement of quality of knowledge of pupils at geography lessons are shown; results of own research are presented.